(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
The objectives of the present study were to define effects on the hypercholesterolemia activity and pharmacokinetics of a novel transdermal proniosomal gel incorporating Lovastatin prepared by coacervation phase separation method. On the basis of the preliminary trials, a 3-factor, 3-level Box–Behnken design was employed to study the effect of Cholesterol, soya lecithin and Tween 80 on dependent variables (particle size, % entrapment efficiency, and % of drug release). Lovastatin optimized proniosomal formulation F1 shown better particle size and % entrapment efficiency and drug release of 99.49% within 24 h in slow and controlled manner when compared with control. The particle size and zeta potential of the optimized lovastatin proniosomal gel was found to be 138.82 nm and -11.4 mV respectively. Optimized batch of Proniosomes was used for the preparation of Lovastatin-based proniosomal hydrogel by incorporating hydrated Proniosomes to Carbopol matrix to enhance the stability and viscosity of the system. From in vivo studies the maximal concentrations (Cmax) of drug was significantly reduced while the areas under the plasma concentration–time curve (AUC) and t1/2 were evidently increased and extended. The results suggest that proniosomes can act as promising carrier which offers an alternative approach for transdermal delivery of Lovastatin. The study demonstrated the effectiveness of proniosomal preparation of Lovastatin for effective management of hypercholesterolemia to reduce risk of cardiovascular disease.